2018
DOI: 10.3851/imp3343
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of the Drug–drug Interaction Potential between Cobicistat-boosted Antiretroviral Regimens and Hormonal Contraceptives

Abstract: Background Cobicistat (COBI), a CYP3A inhibitor, is a pharmacokinetic enhancer that increases exposures of the HIV protease inhibitors (PIs) atazanavir (ATV) and darunavir (DRV). The potential drug interaction between COBI-boosted PIs and hormonal contraceptives, which are substrates of intestinal efflux transporters and extensively metabolized by CYP enzymes, glucuronidation and sulfation, was evaluated. Methods This was a Phase I, open-label, two cohort (n=18/cohort), fixed-sequence study in healthy female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In our cohort study, there were no WLH on concurrent HC and PIs boosted with cobicistat; this combination has been noted to present a potential issue, especially with drospirenone-associated hyperkalemia. 34 …”
Section: Discussionmentioning
confidence: 99%
“…In our cohort study, there were no WLH on concurrent HC and PIs boosted with cobicistat; this combination has been noted to present a potential issue, especially with drospirenone-associated hyperkalemia. 34 …”
Section: Discussionmentioning
confidence: 99%
“…56,57 For patients who are taking darunavir/ritonavir and on COCs, additional contraception may be required due to inadequate hormone levels. 58 Progestin levels may also be affected by ART medications: although a prospective study in 2019, which followed 15 women on ritonavir-boosted protease inhibitors, did not show any difference in ethinyl estradiol concentrations, the authors did find increased levels of levonorgestrel. 59 Likewise, an earlier prospective, nonrandomized trial suggested that norethisterone-based progestin-only contraceptives exhibit increased drug levels when co-administered with ritonavir-boosted protease inhibitors.…”
Section: Combined Hormonal and Progestin-only Oral Contraceptivesmentioning
confidence: 98%
“…61 Another drug-drug interaction of clinical concern is hyperkalemia when drospirenone-containing contraceptives are used along with cobicistat-containing ART regimens. 58 Currently, drospirenone-containing contraceptives are generally contraindicated in users of cobicistat-boosted protease inhibitors when an alternative or additional contraceptive method is available. 19 In terms of the combined hormonal vaginal contraceptive rings, a study in 2019, including 84 women living with HIV, showed that efavirenz decreased etonogestrel levels by 79% and ethinyl estradiol levels by 59%, whereas ritonavir-boosted atazanavir (a protease inhibitor) increased etonogestrel levels by 71% and lowered ethinyl estradiol concentrations.…”
Section: Combined Hormonal and Progestin-only Oral Contraceptivesmentioning
confidence: 99%
See 2 more Smart Citations